Integration of Renewable Energy Resources in Microgrid - Amin, Uzma; Ahmed, Manzar; Aftab, S; Ahmed, Z (Scientific Research Publishing, 2015)
Microgrid is a new concept in power generation. The Microgrid concept assumes a cluster of loads and micro sources operating as a single controllable system that provides both power and heat to its local area. Not much is known about Microgrid behavior as a whole system. Some models exist which describe the components of a Microgrid. In this paper, model of Microgrids with steady state and their transient responses to changing inputs are presented. Current models of a fuel cell, microturbines, wind turbine and solar cell have been discussed. Finally a complete model built of Microgrid including the power sources, their power electronics, and a load and mains model in MATLAB/Simulink is presented.